Laparoscopic lateral suspension combined with uterosacral ligament folding and shortening versus laparoscopic sacrocolpopexy for the treatment of pelvic organ prolapse: a retrospective cohort study - Xiong, Xiangpeng; Xia, Leizhen; Mei, Tong; Huang, Jialv; Wang, Ting; Zhang, Yun; Wang, Shuang; Luo, Ye; Liu, Haiping; Wang, Liqun; Ai, Xiaoyan (Frontiers in Medicine, 2025)
BackgroundPelvic organ prolapse (POP) significantly impacts women's quality of life, with laparoscopic sacrocolpopexy (LSC) considered the gold standard for treatment. However, LSC carries risks of complications, prompting exploration of alternatives. This study compared the efficacy of Laparoscopic Lateral Suspension (LLS) combined with uterosacral ligament folding and shortening (LLS-ULFS) versus LSC for POP treatment.OverviewA retrospective cohort study included 445 women with POP-Q stage ≥ II (LSC group: n=232; LLS-ULFS group: n=213). Surgical outcomes, complications, and patient-reported outcomes were evaluated over a 2-year follow-up period at Jiangxi Maternal and Child Health Hospital.ResultsBoth groups achieved high anatomical success rates (LSC vs. LLS-ULFS): apical (96.98% vs. 94.84%), anterior (94.40% vs. 96.24%), and posterior (96.12% vs. 94.37%) compartments (all P>0.05). The LLS-ULFS group demonstrated superior perioperative outcomes: shorter operation time (85 vs. 105 min, P<0.001), reduced blood loss (40 vs. 50 ml, P<0.001), and lower pain scores (VAS: 4 vs. 4, P<0.001). Long-term follow-up showed significantly better patient-reported outcomes in the LLS-ULFS group for PFDI-20, POPDI-6, CRADI-8, and PISQ-12 scores (all P<0.05), indicating improved quality of life and sexual function. Complication rates were comparable (P>0.05).DiscussionLLS-ULFS achieves anatomical success equivalent to LSC while offering advantages in operative efficiency and recovery. The technique’s avoidance of presacral dissection likely contributes to reduced pain and complications.ConclusionLLS-ULFS is a viable alternative to LSC, providing comparable anatomical correction with superior perioperative outcomes and enhanced quality of life. Its efficacy supports broader clinical adoption for POP management.